2022
DOI: 10.3389/fnut.2022.843360
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Bioactive Compounds in Chicken Cartilage: Protective Effects of Chondroitin Sulfate and Type II Collagen Peptides Against Osteoarthritis Involve Gut Microbiota

Abstract: This study was designed to explore osteoarthritis (OA) treatment from bioactive compounds of chicken cartilage food supplements. The OA rat model induced by sodium iodoacetate was used to evaluate the treatment effect in vivo. In this study, we used animal experiments to show that oral chondroitin sulfate (CS), cartilage powder, and type II collagen peptides could increase the athletic ability of rats and reduce inflammatory cytokine levels in serum or synovial fluid, including prostaglandin E2, tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Of the 38 studies identified in this review, 24 were preclinical in vivo studies ( Table 2 ). Of these, 11 used an OA rat animal model (5 chemically induced OA [ 31 , 32 , 37 , 41 , 43 ], 1 surgically induced OA [ 36 ], 3 high fat diet-induced OA [ 34 , 42 , 44 ], 1 deoxycorticosterone acetate (DOCA) induced [ 46 ] and 1 antibiotic + tryptophan rich diet induced [ 40 ]), 11 used an OA mouse model (7 surgically induced OA [ 26 , 27 , 33 , 35 , 39 , 50 , 51 ], 2 high fat diet induced [ 44 , 45 ], 2 load induced [ 39 , 49 ], 1 used a spontaneous OA model in guinea pigs [ 52 ]) and 1 used a spontaneous OA model in rhesus macaques [ 47 ]. The number of animals used in these studies was variable (range: from 20 to 88) and not reported in a few articles ( n = 3) [ 26 , 31 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 38 studies identified in this review, 24 were preclinical in vivo studies ( Table 2 ). Of these, 11 used an OA rat animal model (5 chemically induced OA [ 31 , 32 , 37 , 41 , 43 ], 1 surgically induced OA [ 36 ], 3 high fat diet-induced OA [ 34 , 42 , 44 ], 1 deoxycorticosterone acetate (DOCA) induced [ 46 ] and 1 antibiotic + tryptophan rich diet induced [ 40 ]), 11 used an OA mouse model (7 surgically induced OA [ 26 , 27 , 33 , 35 , 39 , 50 , 51 ], 2 high fat diet induced [ 44 , 45 ], 2 load induced [ 39 , 49 ], 1 used a spontaneous OA model in guinea pigs [ 52 ]) and 1 used a spontaneous OA model in rhesus macaques [ 47 ]. The number of animals used in these studies was variable (range: from 20 to 88) and not reported in a few articles ( n = 3) [ 26 , 31 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of animals used in these studies was variable (range: from 20 to 88) and not reported in a few articles ( n = 3) [ 26 , 31 , 38 ]. The main technique used to assess OA was histology, which in some studies was also combined with specific semi-quantitative scores (Mankin’s and Osteoarthritis Research Society International (OARSI)) [ 26 , 33 , 37 , 39 , 40 , 50 ] and/or immunohistochemistry [ 33 , 46 ], ramp test [ 32 ], micro-computed tomography [ 27 , 32 , 46 , 49 , 51 ], anterior drawer test, Magnetic Resonance Imaging [ 47 ], and dual-energy X-ray absorptiometry [ 27 ]. Some articles ( n = 5) were designed to test the changes in the gut microbiota and metabolism during the administration of various supplements, such as quercetin, bioactive compounds from chicken cartilage, extracellular vesicles (EVs) from raw milk, oligofructose and prebiotic fiber, for OA [ 26 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another pre-clinical study that compared the effectiveness of Chondroitin sulfate, chicken cartilage powder and collagen peptides in treating OA, it was found that chondroitin sulfate had the most effective therapeutic effect by significantly improving the structure of joint cartilage and reducing OA scores through a decrease in the levels of inflammatory cytokines, such as prostaglandin E2, TNF-α, IL-1b, IL-6, and IL-17, in the serum or synovial fluid. Additionally, chondroitin sulfate increased the presence of Bacteroidetes , a type of bacteria associated with beneficial effects [ 130 ].…”
Section: Gut Microbiota Modulation Strategiesmentioning
confidence: 99%
“…Gut microbiota is symbiotic with host, which affects several vital links, such as nutrition intake, food digestion, systemic metabolism, development of immunity, physiological function maintenance and diseases defense of the human bodies ( 30 , 31 ). Meanwhile, especially in recent years, more and more human and animal studies have indicated the existence of gut-bone axis and suggested that GM and its metabolites are closely involved in the pathogenic process of OA, which might become a potential and promising intervention target ( 32 , 33 ). On this basis, Gleason et al ( 34 ) emphasized the role of gut-joint axis in the pathogenic process of OA, and recognized that the gut-joint axis was proposed as an association involving the gastrointestinal microbiome, immune and inflammatory response that it induced, and the overall joint health.…”
Section: The Close Correlation Between Osteoarthritis Obesity and Gut...mentioning
confidence: 99%